2014
DOI: 10.1007/s10396-014-0533-0
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of peripheral intraneural microhemodynamics evaluation by using contrast-enhanced ultrasonography

Abstract: High intra-observer, inter-observer, and inter-examination reproducibility of CEUS was obtained in the evaluation of the intraneural enhancement pattern when the region of interest was placed in the proximal region of the median nerve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Normalized data were obtained for each wrist relative to the baseline value by using the average from the first approximately 18 seconds. The high reproducibility of CEUS confirmed by previous data allowed us to examine the blood flow proximal to the carpal tunnel in patients with CTS …”
Section: Methodsmentioning
confidence: 52%
See 4 more Smart Citations
“…Normalized data were obtained for each wrist relative to the baseline value by using the average from the first approximately 18 seconds. The high reproducibility of CEUS confirmed by previous data allowed us to examine the blood flow proximal to the carpal tunnel in patients with CTS …”
Section: Methodsmentioning
confidence: 52%
“…Although blood flow within the median nerve has been evaluated by color Doppler US in patients with CTS, it is difficult to detect low‐volume blood flow in the subsynovial connective tissue by using conventional methods. Although Evans et al reported reliable and valid techniques using CEUS for measuring vascularity associated with nerve disorders in animal models, we have recently demonstrated the high reproducibility of CEUS of the microcirculation in humans; in this study, we evaluated the blood flow in the subsynovial connective tissue proximal to the carpal tunnel for the first time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations